Sources for the history of emotions
1 online resource.
Keywords: "Offering insights on the wide range of sources that are available from across the globe and throughout history for the study of the history of emotions, this book provides students with a handbook for beginning their own research within the field. Written by key scholars, it shows readers how different sources can be used to extract information about the history of emotions, highlighting the kind of data available and how it can be used in a field for which there is no convenient archive of sources. The focused discussion of sources, which not only builds on existing research, but encourages further efforts, makes it a key resource for all students of emotions history"--